2015
DOI: 10.4103/2008-7802.172376
|View full text |Cite
|
Sign up to set email alerts
|

Body composition in type 2 diabetes: Change in quality and not just quantity that matters

Abstract: Background:Deranged body fat and muscle mass are aftermaths of uncontrolled diabetes. Anthropometric methods like body mass index (BMI) do not give qualitative inferences like total body fat (TBF), visceral fat (VF) or subcutaneous fat (SF) that can be given by bio-electrical impedance analysis (BIA). We studied body composition of type 2 diabetics in comparison to controls matched by age-sex, weight and BMI separately.Methods:Seventy-eight under-treatment type 2 diabetics of either sex with known glycemic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 21 publications
5
31
0
4
Order By: Relevance
“…Furthermore, the SMM/VFA ratio could be used to predict T2D and MetS with high sensitivity and specificity. Consistent with our results, Solanki et al 33 have found that individuals with T2D had significantly higher PBF, FM, visceral fat, and subcutaneous fat than nondiabetic controls. Moreover, both quantitative and qualitative increases in fat mass were observed.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the SMM/VFA ratio could be used to predict T2D and MetS with high sensitivity and specificity. Consistent with our results, Solanki et al 33 have found that individuals with T2D had significantly higher PBF, FM, visceral fat, and subcutaneous fat than nondiabetic controls. Moreover, both quantitative and qualitative increases in fat mass were observed.…”
Section: Discussionsupporting
confidence: 93%
“…In a study, we found that type 2 diabetics have more ectopic fat on the expense of skeletal muscle that persists even after matching by weight or BMI, both quantitatively and qualitatively. [ 20 ] Hence, correlation of BMI and PAD should be seen even seriously as real correlation between qualitative body fat and PAD can be even stronger. Excess BMI and ectopic distribution is seen as a fore-runner of insulin resistance which can lead to type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been various epidemiological studies to determine the association between body composition indicators and risk of T2DM in other countries [14][15][16], no such study has been performed in China, the most populated country in the world.…”
Section: Introductionmentioning
confidence: 99%